Codes of Ethics Among Corporate Research Departments, Marketing Research Firms, and Data Subcontractors: An Examination of a Three-Communities Metaphor - Ferrell, O. C. (Journal of business ethics, 1998)
Despite the importance of the interorganizational nature of the marketing research process, very little research has addressed how research organizations differ and how they affect each other in the conduct of ethical marketing research. The purpose of this study is to examine differences among three typical participants in the research process: corporate research departments, marketing research firms, and data subcontractors. These organizations were examined with respect to having and enforcing internal codes of conduct and the awareness and enforcement of external codes of conduct. By exploring these differences, this study should help marketing researchers better understand the relationships among participants in the research process. Understanding these differences is the first step toward controlling the potential for ethical conflict among research participants.